2012
DOI: 10.1590/s1984-29612012000100005
|View full text |Cite
|
Sign up to set email alerts
|

Biological parameters of cattle ticks fed on rabbits

Abstract: With the objective of encouraging the use of rabbits as alternative hosts for the cattle tick, four rabbits were infested on the ears and back. From the second day of infestation the developmental stages were observed. The duration of larval engorgement and changes were estimated between six and eight days in the region of the back and between five and seven days in the pinna. The nymphal engorgement and changes occurred at approximately 10.80 ± 2.65 days in the dorsal and 11.00 ± 2.52 days in the ear, with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
13
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 7 publications
2
13
2
Order By: Relevance
“…The egg incubation period of R. microplus was 22 -31 days. This is consistent with the findings of Amaral et al (2012;19 -26 days). However, Joydhar et al, in 2010 have reported shorter incubation periods of 9 -18 days.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The egg incubation period of R. microplus was 22 -31 days. This is consistent with the findings of Amaral et al (2012;19 -26 days). However, Joydhar et al, in 2010 have reported shorter incubation periods of 9 -18 days.…”
Section: Discussionsupporting
confidence: 93%
“…Pre-oviposition and oviposition periods for R. microplus were 5.5 ± 0.8 days and 8.0 ± 2.4 days, respectively. Similar results have been reported in other studies of Joydhar et al (2010), who reported 5.5 ± 0.1 days and 6.0 ± 0.1days and Amaral et al (2012) recorded 3.85 ± 1.80 days and 5.55 ± 1.8 days while Benitez et al (2012) recorded 3 ± 0 days and 6.7 ± 1.4 days of pre-oviposition and oviposition periods, respectively. Although Gallardo and Morales (1999) reported a similar pre-oviposition period of 4.74 days for R. microplus and their oviposition period is as long as 23.49 days.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…It is considered that R. microplus has high specificity for cattle and is only found on other animals that usually appear with infested cattle, such as goats, sheep, camels, horses, donkeys, pigs, dogs, and some of wildlife deer and rodents [ 15 , 16 , 21 ]. Biological parameters of R. microplus fed on goats, horses, and rabbits were also analyzed in some literatures [ 22 - 25 ]. However, few of them compared the biological parameters of R. microplus fed on different hosts at the same conditions, which is important for evaluating the suitability of them as experimental animals in the research of R. microplus control techniques.…”
Section: Discussionmentioning
confidence: 99%
“…Do Amaral et al [ 22 ] infested 4 rabbits with R. microplus in/on the ear and back. The recovery of engorged female ticks from backs was 4.9%, similar to that of our study (5.5%), but it was 10.7% from ears, similar to that of cattle in the present study (11.0%), which suggests that tick recovery is significantly associated with the infestation region on the host.…”
Section: Discussionmentioning
confidence: 99%